PENERAPAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) BERBANTUAN FILM DOKUMENTER DALAM MENANAMKAN NILAI NASIONALISME DAN MENINGKATKAN HASIL BELAJAR PADA SISWA SEKOLAH DASAR - Sutaryanto Sutaryanto (Universitas PGRI Madiun, 2015)
This research is conducted to integrate the model, review the process andresults of the model application,and analyze the differences between theapplication of students learning outcomes using learning model VCT assisted thedocumentary film with conventional learning in social studies. This research is akind of mixed methods with experimental design. The data is derived usingobservation, documentation, attitude scale, and tests. The application of the ValueClarification Technique (VCT) models assisted the documentary film is veryeffective. It can be seen from the teacher’s observation, student attitudes, analysisof students' worksheet, students response with very good criteria, and the resultsshow the attitude scale test of the Value Clarification Technique (VCT) modelsassisted the documentary film effectivein instilling the value of nationalism. Thereis a difference in student learning outcomes between experimental and controlclasses. Student learning outcomes experimental class are higher than the controlclass.